Life-history, substrate choice and Cytochrome Oxidase I variations in sandy beach peracaridans along the Rio de la Plata estuary. (5th March 2017) - Fanini, L.; Zampicinini, G.; Tsigenopoulos, C.S.; Barboza, F.R.; Lozoya, J.P.; Gómez, J.; Celentano, E.; Lercari, D.; Marchetti, G.M.; Defeo, O.
Abstract: Life-history, substrate choice and Cytochrome Oxidase I (COI) sequences were analysed in populations of two peracaridans, the supralittoral talitrid Atlantorchestoidea brasiliensis and the intertidal cirolanid Excirolana armata . Three populations of each species, from beaches with similar grain size and located at different points along the natural gradient generated by the Rio de la Plata estuary were analysed. Abundance of E. armata increased with distance from the estuary, while the opposite trend was observed for A. brasiliensis . The proportion of females decreased towards high salinities for both species, significantly for E. armata . A test on substrate salinity preference revealed the absence of patterns due to active choice in E. armata . By contrast, A. brasiliensis showed no preference for the population closer to the estuary, while individuals from the other two sites significantly preferred high salinity substrates. Mitochondrial COI sequences were obtained from A. brasiliensis specimens tested for behaviour. Sequence analysis showed the population from the intermediate site to differ significantly from the other two. No significant genetic differentiation was instead found between populations from the two most distant sites, nor between individuals that expressed different salinity preference. Results showed that diverse sets of traits at the population level enable sandy beach species to cope with local environmental changes: life-history and behavioural traits appear to change in response to different ecological conditions, and, in the case of A brasiliensis, independently of the population structure inferred from COI sequence variation. Information from multiple traits allowed detection of population profiles, highlighting the relevance of multidisciplinary information and the concurrent analysis of field data and laboratory experiments, to detect responses of resident biota to environmental changes.